Condition of platelet homeostasis in patients with hypertension and its combination with ischemic heart disease - Пастушина, Анна Ігорівна (ScienceRise: Medical Science, 2016)
Aim of the work is in assessment of spontaneous and induced aggregation in patients with hypertension and revelation of features of aggregative activity of platelets at combination of hypertension with ischemic heart disease. Methods of research: special laboratory studies: spontaneous aggregation of platelets with arachidonic acid, adenosine diphosphate, collagen and adrenalin. Results of research: in the result of the work was revealed the high level of spontaneous aggregation of platelets in both studied groups. It was established, that associated course of hypertension and IHD is attended by preservation of the sufficiently high functional activity of platelets despite the antiplatelet treatment that is typical for patients with hypertension of both II and III stages. Platelets of patients with hypertension of III stage with concomitant IHD even under conditions of aggressive antiplatelet treatment stay more reactive that is manifested in preservation of the high level of spontaneous aggregation and adrenalin-induced aggregation in subgroup of patients who do not receive ß-adrenoblockers